Towards enhanced creativity in fashion: integrating generative models with hybrid intelligence - Ryjov, Alexander; Kazaryan, Vagan; Golub, Andrey; Egorova, Alina (Frontiers in Artificial Intelligence, 2024)
IntroductionThis study explores the role and potential of large language models (LLMs) and generative intelligence in the fashion industry. These technologies are reshaping traditional methods of design, production, and retail, leading to innovation, product personalization, and enhanced customer interaction.MethodsOur research analyzes the current applications and limitations of LLMs in fashion, identifying challenges such as the need for better spatial understanding and design detail processing. We propose a hybrid intelligence approach to address these issues.ResultsWe find that while LLMs offer significant potential, their integration into fashion workflows requires improvements in understanding spatial parameters and creating tools for iterative design.DiscussionFuture research should focus on overcoming these limitations and developing hybrid intelligence solutions to maximize the potential of LLMs in the fashion industry.